From Overt to Tacit Collusion - Jeroen Hinloopen; Adriaan Soetevent (Tinbergen Institute, 2008)
Recent laboratory experiments support the popular view that the introduction of corporate leniency programs has significantly decreased cartel activity. The design of these repeated game experiments however is such that engaging in illegal price discussions is the only way for subjects to avoid the one-shot competitive equilibrium. Subjects in the experiment of this paper have multiple feasible Nash equilibrium strategies to avoid the competitive equilibrium. These strategies differ in the difficulty of the coordination problem they have to solve. The experimental results show that if the efforts of the antitrust authority and the leniency program are directed exclusively to the most straightforward collusive scheme, subjects manage to switch to a more intricate form of coordination. This shift from overt collusion to tacit collusion questions the acclaimed success of corporate leniency programs.
Keywords: C72; C92; L41; 330; overt collusion; tacit collusion; corporate leniency program; antitrust policy; Nichtkooperatives Spiel; Straffreiheit; Wettbewerbspolitik; Wiederholte Spiele; Nash-Gleichgewicht; Test; Theorie